From Sanderson's to Alley's : a biography of the West Tisbury General Store - Parton, Charles (Barnardsville, NC : Carter Hill Farm, 1992)
In the guise of telling the story of Alley's, the author has also illuminated island history and the unsettling but inevitable process of change.
Keywords: General stores -- History. -- Massachusetts; West Tisbury (Mass.) -- History; Martha's Vineyard (Mass.) -- History